2019
DOI: 10.33595/2226-1478.10.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Problem Based Learning as strategy for the development of competences in secondary education students

Abstract: The methodological strategies Plough to set of activities that allow learning to be achieved and make activate and dynamic teaching possible taking into account the needs of the context, the Problem Based Learning (hereinafter ABP), is to strategy that starts from to problem to generate student learning, in that sense, the objective of this research was to determine the ABP strategy, that allows to develop competences: inquire through scientific methods to build knowledge and explains the physical world based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Al-Busaidi et al (2021) highlight the need for collaboration in developing a problem-based learning culture in institutions. Similarly, Casa Coila et al (2019) found that using a problem-based learning methodology for competency acquisition improved students' learning. Similarly, Yew and Goh (2016) demonstrated the effectiveness of problem-based learning in their review of more excellent long-term knowledge retention and improved knowledge application.…”
Section: Experiential Learning and Outdoor Trainingmentioning
confidence: 95%
See 1 more Smart Citation
“…Al-Busaidi et al (2021) highlight the need for collaboration in developing a problem-based learning culture in institutions. Similarly, Casa Coila et al (2019) found that using a problem-based learning methodology for competency acquisition improved students' learning. Similarly, Yew and Goh (2016) demonstrated the effectiveness of problem-based learning in their review of more excellent long-term knowledge retention and improved knowledge application.…”
Section: Experiential Learning and Outdoor Trainingmentioning
confidence: 95%
“…An increasing number of studies have focused on problem-based learning, and its applications are being located (Al-Busaidi et al, 2021;Casa Coila et al, 2019;Yew & Goh, 2016). Al-Busaidi et al (2021) highlight the need for collaboration in developing a problem-based learning culture in institutions.…”
Section: Experiential Learning and Outdoor Trainingmentioning
confidence: 99%
“…El aprendizaje basado en problemas (ABP). Para Carranza (2017); Morales, (2017); Ali (2019); Luy-Montejo (2019); Casa et al (2019); Cyrulies y Schamne (2021) el ABP es un método en el que los alumnos aprenden a través de problemas complejos y abiertos del mundo real que fomentan el aprendizaje de los estudiantes a través de principios y conceptos y se motivan a investigar al pasar el docente de expositor a guía y el estudiante descubre nuevas cosas, con lo cual desarrolla habilidades de pensamiento crítico, soluciona problemas, se comunica fluidamente y emprende un aprendizaje permanente.…”
Section: Variableunclassified
“…En consecuencia, se aplica el modelo de Aprendizaje Basado en Problemas (Méndez Urresta, Méndez Urresta, & Méndez Carvajal, 2017) como estrategia didáctica viable para que el estudiante logre obtener los conocimientos y la experticia que propone la asignatura. El ABP, como también se le conoce, permite enfrentar de manera innovadora e interactiva la resolución de problemas complejos de la realidad (Casa, Huatta, & Mancha, 2019) desde un ambiente académico mediante un proyecto de trabajo en el cual los grupos de trabajo definen un tema, plantean preguntas, las debaten, recolectan datos, los analizan, reflexionan sobre su aprendizaje, y generan conclusiones y productos para luego socializarlos.…”
unclassified